Comparison of the Multiple Platforms to Identify Various Aeromonas Species - Du, Xiaoli; Wang, Mengyu; Zhou, Haijian; Li, Zhenpeng; Xu, Jialiang; Li, Zhe; Kan, Biao; Chen, Daoli; Wang, Xiaoli; Jin, Yujuan; Ren, Yan; Ma, Yanping; et al. (Frontiers in Microbiology, 2021)
We compared several identification methods for Aeromonas genus members, including traditional biochemical testing, multiplex-PCR amplification, mass spectrometry identification, whole-genome sequencing, multilocus phylogenetic analysis (MLPA), and rpoD, gyrA, and rpoD-gyrA gene sequencing. Isolates (n=62) belonging to the Aeromonas genus, which were came from the bacterial bank in the laboratory, were used to assess the identification accuracy of the different methods. Whole-genome sequencing showed that the Aeromonas spp. isolates comprised A. caviae (n=21), A. veronii (n=18), A. dhakensis (n=8), A. hydrophila (n=7), A. jandaei (n=5), A. enteropelogenes (n=2), and A. media (n=1). Using the whole-genome sequencing results as the standard, the consistency of the other methods was compared with them. The results were 46.77% (29/62) for biochemical identification, 83.87% (52/62) for mass spectrometric identification, 67.74% (42/62) for multiplex-PCR, 100% (62/62) for MLPA typing, 72.58% for gyrA, and 59.68% for rpoD and gyrA-rpoD. MLPA was the most consistent, followed by mass spectrometry. Therefore, in the public health laboratory, both MLPA and whole-genome sequencing methods can be used to identify various Aeromonas species. However, rapid and relatively accurate mass spectrometry is recommended for clinical lab.